The Policy of the Prosecutor's Authority in Termination of Prosecutions based on Restorative Justice in Criminal Justice System In Indonesia - Laksamana Bagas Dewandaru; Jawade Hafidz; Latifah Hanim (Universitas Islam Sultan Agung, 2022)
This study aims to determine the policy of the prosecutor's authority in terminating prosecution based on restorative justice in the criminal justice system, namely based on the principle of opportunity, namely the Prosecutor's Office is the only State Institution controlling cases or has the authority to continue or not file cases to the Court based on the provisions of the Act. This authority is implied in the form of the Attorney General's Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. The approach method used is normative juridical. Specifications are descriptive analytical. The type of data is secondary data, divided into legal materials derived from law and legal science. The method of data collection through literature study and interviews with the data analysis method is qualitative analysis. The Prosecutor's Law is included in attribution, namely the granting of government authority by lawmakers to government organs. In Islamic criminal theory, the authority to stop prosecution based on restorative justice is included as special prevention and according to the history of Islamic development, it is included in the rehabilitation of the criminal. In the research conducted by the researcher, it was found that there were obstacles in stopping prosecution based on restorative justice at the Banggai District Prosecutor's Office, namely based on the decree of the Banggai District Attorney Number B-748/P.2.11/Eoh.2/11/2021, namely the distance traveled by the parties involved. The case with the Banggai District Prosecutor's Office is quite far away, with the condition of the road infrastructure being unfavorable. The crime committed is domestic violence which makes it difficult for peaceful efforts to be carried out, so that the time allotted is very limited. If drawn from the theory of law enforcement, these obstacles are included in the legal culture and legal substance.